The Relationship Between Noise Level and Sleep Quality of Wood Processing Workers - Haryawan, I Gusti Agung; Biomi, Agnes Ayu; Suadnyana, Ida Ayu Astiti (GLOBAL HEALTH SCIENCE GROUP, 2024)
Wood processing generally involves the use of large machines for cutting and grinding. This process is customized according to consumer needs. During wood processing, workers are exposed to noise generated by machines, with an average level exceeding 85 dBA. These workers typically work eight hours a day with a one-hour break. The impact of this noise extends beyond hearing loss, as it also disrupts the workers' sleep quality. This study aims to examine the relationship between noise levels and sleep quality among wood processing workers, specifically at UD. Adhi Santa in Tabanan, Bali, which serves as the research site. The study design employed was a cross-sectional study with a sample population of 40 wood processing workers who met the inclusion and exclusion criteria. Noise levels were measured using a sound level meter in the work machine area, while sleep quality was assessed using the Pittsburgh Sleeping Quality Index (PSQI). The data were analyzed using computer software, utilizing Spearmans to determine the significant relationship between noise levels and sleep quality among workers in the wood processing factory. The results indicated that, out of the 40 workers, the analysis revealed a significant relationship between noise levels and sleep quality (p = 0.002, p < 0.05). In conclusion, it can be stated that there is indeed a significant relationship between noise levels and sleep quality among wood processing workers.